Peranan Gambar Pada Tempat Sampah dalam Meningkatkan Frekuensi Membuang Sampah Siswa SDN Tahunan, Kecamatan Umbulharjo, Kota Yogykarta, Tahun 2015 - Junaidi Junaidi; Adib Suyanto; Sigid Sudaryanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2015)
Waste management activity may involves the entire community, including children. To teachchildren as early as possible is a good start to get them used to dispose wastes in appropriateplaces since they are easier to understand and able to implement. The study used three figures of cartoon character onto waste bins to know which one is the best for get the attention ofstudents of Tahunan Elementary School of Yogyakarta City and so that influencing the frequency of their waste disposal. The study was a quasi experiment with post test only design andthe object of the study was the entire 336 students of SDN Tahunan. The observation of wastedisposal was conducted daily in 10 days between 7 to 11 a.m. and the statistical result of oneway anova test at 95 % confidence level came to conclusion that the differences among wastedisposal frequencies between the three figures was significant (p-value=0,027), and from theLSD test it was found that students were most interested to Doraemon picture.